The relationship between the degree of low back pain and concentration levels among RICCI Catholic High School Jakarta students during the COVID-19 pandemic - Putu Radhya Kirana Karmanita; Heidy; Nelson Sudiyono; Mariani Santosa (Published by Universitas Gadjah Mada, 2025)
The COVID-19 pandemic has shifted most learning activities to an online format, leading to increased sitting time and a higher risk of low back pain (LBP). Low back pain can be a factor that causes changes in concentration during learning. This study aimed to evaluate the relationship between the degree of LBP and the level of learning concentration in high school students. It was a cross-sectional study conducted at RICCI Catholic High School Jakarta, involving students from grades 10, 11, and 12. Data were collected using a questionnaire that was distributed online with Google forms. The Chi-square method for data analysis was used with a significance level of 0.05. A total of 121 students participated in this study, with 66.9% did not experience LBP, 30.6% had LBP with a slight degree of pain, and 2.5% had LBP . There were no students with severe LBP. The results for low, moderate and high concentration levels were 8.3%, 70.2%, and 21.5%, respectively. The bivariate analysis between LBP and learning concentration level using was 0.062 (p>0.05). In conclusion, there is no significant relationship between the degree of LBP and the level of concentration in high school students.